PECULIARITIES OF RAISING A DISABLED CHILD IN THE FAMILY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Our future depends on the young people we are raising today. The family is the foundation that fulfills such a huge task and creates material and spiritual wealth. The family, as the primary social unit of society, has a complex structure, and in its activities, it reflects not only the needs and abilities of family members, the goals and tasks of their various activities, but also their educational activities.